Kewaspadaan nasional dan bahaya laten komunis - Dinuth, Alex. ([Jakarta] : Intermasa, 1997)
Analysis of latent subversive activities of communism in Indonesia; collection of articles.
Includes bibliographical references and index.
Keywords: Communism -- Indonesia; Subversive activities -- Indonesia; Indonesia -- Politics and government -- 20th century